(untitled) (Journal of Educational Sciences, 2017)
In the article presents scientific and methodical analysis about new ways of teaching the subject “Self-cognition” in secondary schools. Characterizing features of spiritually-moral program “Self-cognition” the author makes a review of the history of teaching the subject at all levels of the system of General secondary education as a compulsory subject. The history of teaching of the subject is a divided into three periods. In the first period refers to the experiment in all regions of our country to implement the program of spiritual and moral education. In the second period seen the introduction of self-discovery at all levels of secondary school as compulsory subject and on the preparation of state standard of the subject, development of textbooks and teaching-methodical complexes on the subject. In addition, in the third period analyzed the content and structure of the subject in new directions today. The author also gives a description of the eternal universal values, and about their place in humane pedagogy. The author reveals the essence of such values as truth, love, righteous conduct, inner peace and non-violence, and identifies three conditions of teaching the subject in new directions.